Pengembangan Game Edukasi 2D Kosakata Dasar Bahasa Inggris untuk Siswa Kelas 2 SDN Maduretno 1 - Rama Maulana (Fakultas Ilmu Komputer, 2026)
This research was conducted based on the low mastery of basic English vocabulary among second-grade students at SDN Maduretno 1 and the limited use of learning media, which was still dominated by textbooks and whiteboard-based instruction. Such conditions made students easily bored and less actively involved in the learning process. This study aimed to develop a 2D educational game for basic English vocabulary based on Android, determine its feasibility as a learning medium, and examine its effectiveness in improving students’ vocabulary mastery. The research method used was Research and Development (R&D) with the ADDIE development model, consisting of analyze, design, development, implementation, and evaluation stages. The product was developed using Unity and presented vocabulary materials related to objects around students, animals, colors, and numbers. Data were collected through observation, interviews, questionnaires, expert validation, and pretest-posttest assessments. The results showed that the developed educational game consisted of learning menus, playing menus, game levels, question pop-ups, scoring systems, audio, and learning feedback. The material expert validation obtained a score of 98% in the very feasible category, while the media expert validation obtained a score of 90% in the very feasible category. Student responses reached 88.93%, categorized as very positive. The effectiveness test showed that the experimental class achieved an N Gain score of 0.74 in the high category, while the comparison class obtained an N Gain score of 0.49 in the medium category. Therefore, the developed Android-based 2D educational game is very feasible and more effective in helping students understand and remember basic English vocabulary in an interactive and enjoyable way.
FINALISASI oleh Arif 2026 Juli 13
Keywords: Game Edukasi 2D; Kosakata Bahasa Inggris; Sekolah Dasar; Andorid; ADDIE